Chemical Genetics Approach Identifies Abnormal Inflorescence Meristem 1 as a Putative Target of a Novel Sulfonamide That Protects Catalase2-Deficient Arabidopsis against Photorespiratory Stress - van der Meer, Tom; Verlee, Arno; Willems, Patrick; Impens, Francis; Gevaert, Kris; Testerink, Christa; Stevens, Christian V; Van Breusegem, Frank; Kerchev, Pavel (Cells, 2020)
Alterations of hydrogen peroxide (H2O2) levels have a profound impact on numerous signaling cascades orchestrating plant growth, development, and stress signaling, including programmed cell death. To expand the repertoire of known molecular mechanisms implicated in H2O2 signaling, we performed a forward chemical screen to identify small molecules that could alleviate the photorespiratory-induced cell death phenotype of Arabidopsisthaliana mutants lacking H2O2-scavenging capacity by peroxisomal catalase2. Here, we report the characterization of pakerine, an m-sulfamoyl benzamide from the sulfonamide family. Pakerine alleviates the cell death phenotype of cat2 mutants exposed to photorespiration-promoting conditions and delays dark-induced senescence in wild-type Arabidopsis leaves. By using a combination of transcriptomics, metabolomics, and affinity purification, we identified abnormal inflorescence meristem 1 (AIM1) as a putative protein target of pakerine. AIM1 is a 3-hydroxyacyl-CoA dehydrogenase involved in fatty acid β-oxidation that contributes to jasmonic acid (JA) and salicylic acid (SA) biosynthesis. Whereas intact JA biosynthesis was not required for pakerine bioactivity, our results point toward a role for β-oxidation-dependent SA production in the execution of H2O2-mediated cell death.
Keywords: Photosynthesis; Plant Leaves; signální transdukce; fyziologický stres; Signal Transduction; proteiny huseníčku; chemical genetics; Cyclopentanes; buněčné dýchání; H2O2 signaling; buněčná smrt; sulfonamidy; kyselina salicylová; Arabidopsis Proteins; Hydroponics; regulace genové exprese u rostlin; listy rostlin; výpočetní biologie; cyklopentany; Gene Expression Regulation, Plant; hydroponie; Stress, Physiological; photorespiration; Arabidopsis; Computational Biology; Seeds; oxylipiny; Oxylipins; peroxid vodíku; semena rostlinná; stanovení celkové genové exprese; Plant Cells; transkriptom; Salicylic Acid; Transcriptome; Cell Respiration; meristém; abnormal inflorescence meristem 1; Gene Expression Profiling; fotosyntéza; Cell Death; catalase2-deficient Arabidopsis; Hydrogen Peroxide; Meristem; Sulfonamides; multienzymové komplexy; Multienzyme Complexes; rostlinné buňky